On state of commercial herd of chum salmon Oncorhynchus keta and forecasting its abundance at Iturup Island - A. N. Elnikov; O. V. Zelennikov (Известия ТИНРО)
Population dynamics and size-age structure are analyzed for the chum salmon herd formed in the Prostor and Kurilsky Bays of Iturup Island (Kuril Islands). Release of chum juveniles into the waters of the bays increased from 10.7.106 ind. in 1996 to 197.6.106 ind. in 2020. The catch of adults was closely related with the release of juveniles (r = 0.66) and increased from 800 t in 1996 to 18,968 t in 2019. Year-to-year dynamics of the chum salmon catch coincides in these two bays, i.e. strong year-classes provide good catch in both bays and low survival causes low catch everywhere. The spawners of age groups 2+ and 3+, mostly 3+ (62 %, on average) dominated in the catches in 2014–2022. This feature makes available the forecast of chum salmon landing in the Prostor and Kurilsky Bays because of strong dependence of annual catch of fish at the age 3+ on the catch at the age 2+ in preceding year (r = 0.89; rs = 0.98). Besides, a significant relationship is noted between the annual catches of chum and pink salmon belonged to the same year-class, i.e. between the catches of chum salmon at the age 3+ and the catches of pink salmon in preceding year (r = 0,71; rs = 0,75).